Respon Pertumbuhan Dan Produksi Tanaman Kangkung (Ipomoea reptans Poir) Melalui Pemberian POC Limbah Ikan Yang Difermentasi - Kamsia Dorliana Sitanggang (UNIVERSITAS LABUHANBATU, 2019)
The fish waste can be utilized to be one of the profitable products, including Liquid Organic Fertilizer (POC). Utilization of POC rich in macro and micro elements is expected to increase the growth and production of Ipomoea reptans Poir. In this study studied the technique of processing fish waste into Liquid Organic Fertilizer and apply it to Ipomoea reptans Poir. The results showed that POC of fish waste in kangkung plants with 10, 20, and 30 mL doses significantly increased plant height compared to without POC, and the best result was obtained in POC 30 mL because it can increase plant height growth from 29,35 cm (control) to 32.75 cm. The provision of POC in the number of leaves increase no significant effect. Unlike the case with the observation of Fresh Weight Plant after the provision of POC-based waste fish. The results showed that POC was significantly influenced by observation of fresh weight of plant, where the highest weight (113,33 gram) was obtained at kangkung plant after POC 30 ml, while the lowest (47,66 gram) was shown by plant without POC. Keywords: Ipomoea reptans, Fish Waste, Liquid Organic Fertilizer (POC)